The Impact of Financial Technology Adoption and Financial Literacy on MSME Business Sustainability : SEM-PLS Analysis - Widyawati, Nur (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the Indonesian economy. MSMEs contribute to creating jobs, increasing people’s income, and encouraging local economic growth. However, many MSMEs in Indonesia still face various challenges in running their business. One of the main challenges is limited access to capital and financial management capabilities. In this digital era, Financial Technology (Fintech) is present as an innovative solution to help MSMEs overcome these challenges. Fintech offers a variety of financial services that are easily accessible and affordable for MSMEs, such as online loans, digital payment systems and financial management platforms. Apart from Fintech, financial literacy is also an important factor in the sustainability of MSMEs businesses. Financial literacy is an individual’s ability to understand and manage their finances well. With good financial literacy, MSMEs can make the right financial decisions to increase the profitability and sustainability of their business. This research aims to determine the effect of financial technology adoption on business sustainability with financial literacy as a moderating variable. The analysis technique used was structural equation modeling based on partial least squares with 30 MSME respondents. The results obtained in this research are that the adoption of financial technology has not an effect on business sustainability with financial literacy as a moderating variable.